Estrogenic and anti-androgenic endocrine disrupting chemicals and their impact on the male reproductive system - De Falco, Maria; Forte, Maurizio; Laforgia, Vincenza (Frontiers in Environmental Science, 2015)
Endocrine disrupting chemicals (EDCs) are identified for their ability to perturb the homeostasis of endocrine system and hormonal balance. The male reproductive system is under close control of hormones and each change in their concentration and time of exposition and action can induce a deregulation of its physiology. In this review we summarize the most recent studies on two main categories of EDCs with different action: the estrogenic bisphenol A and alkylphenols and the anti-androgenic phthalates. This review describes the main effects of these substances on male reproductive system.